Determination of UDP-Glucose and UDP-Galactose in Maize by Hydrophilic Interaction Liquid Chromatography and Tandem Mass Spectrometry - Chen Lan; Bing Zhao; Lu Yang; Yusen Zhou; Siyi Guo; Xuebin Zhang; Junli Zhang (Journal of Analytical Methods in Chemistry)
Nucleotide sugars, the activated forms of monosaccharides, are important intermediates of carbohydrate metabolism in all organisms. Here, we describe a method for the detection and quantification of UDP-glucose and UDP-galactose in maize in order to compare their metabolism in both wild-type and mutated plants. Triple quadrupole operating in a multiple reaction monitoring mode was used to quantify nucleotide sugars. The limits of detection for UDP-glucose and UDP-galactose were 0.50 and 0.70 ng·mL−1, respectively. The recoveries of the method ranged from 98.3% to 103.6% with the relative standard deviations less than 6.3%. To prove the applicability of this method, we analyzed several sets of maize extracts obtained from different cultivars grown under standardized greenhouse conditions. All the results demonstrated the suitability of the developed method to quantify UDP-glucose and UDP-galactose in maize extracts.